Design and operation of renewable energy sources based hydrogen supply system: Technology integration and optimization. (April 2017) - Won, Wangyun; Kwon, Hweeung; Han, Jee-Hoon; Kim, Jiyong
Abstract: The benefits of hydrogen as a clean and efficient fuel can be realized fully only when hydrogen is produced from renewable energy sources (RES). In this study, a new methodology is proposed to identify the optimal configuration and operation of an RES-based hydrogen supply system. The key is a superstructure-based optimization model using mixed-integer linear programming (MILP), which can integrate multiple resources and various technologies, such as electricity generation (e.g., wind turbine, photovoltaic panel, and dish-stirling power systems) and hydrogen production technologies (e.g., water splitting using alkaline electrolyzer and biomass gasifier), to minimize the total annual cost. The performance of the proposed methodology was validated through an application study on Jeju Island, Korea. In the case study, process economics and main cost drivers were analyzed. In addition, the effect of integration of technologies along with different resources on the economics was discussed. Highlights: We develop a network optimization model for hydrogen supply system from renewable energy sources. We include diverse energy sources and corresponding technologies. We identify the optimal system configuration and operational strategy of hydrogen supply system. We apply the proposed model to the design problem of the energy system of Jeju Island, Korea.